Organizational-level study of the impact of past turnover on future turnover in the Sultanate of Oman. - Mohamed Al Balushi, Ruqaiya; Idris, Khairuddin; Omar, Zoharah; Basri, Ramli; Kumar, Naresh (Consortia Academia Publishing, 2013)
Turnover phenomena attracted researchers from all over the world for generations. Most of this research was directed towards turnover antecedents with a few scattered conceptual and empirical studies related to turnover consequences. The purpose of this study is to investigate the impact of past turnover on future turnover in public organizations, in addition to test the mediation role of organizational climate in this relationship. Public schools as separate identities were the best choice as the study sample. Data were collected through questionnaires from 142 public schools in all educational regions in Oman. Two-step structural equation modeling approach, and nested model comparison were used for data analysis. The results revealed that: (1) past turnover predicts future turnover, significantly; (2) organizational climate fails to mediate this relationship. The study added to the body of knowledge by confirming Staw’s hypothesis relating past turnover to future turnover in the Omani context. Human resource professionals and educational administration practitioners may play an important role in decreasing future turnover by tackling and decreasing past turnover, in addition to improving the relationship climate in schools. The study is limited to public schools in Oman and further studies about turnover consequences in the Arabic context are needed to affirm the results.